Hubungan Pengetahuan Diet Hipertensi terhadap Kepatuhan Diet pada Penderita Hipertensi di Puskesmas Wundulako - Mariana, Mariana; Indriastuti, Diah; Abadi, Ellyani (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2022)
Hypertension is a risk factor that has a lot of influence on the occurrence of blood vessels and heart disease. Compliance is the word used to define the patient's attitude in taking medication properly both in terms of dose, frequency and time. Knowledge is a process that results from curiosity through the senses, especially the eyes and ears to certain objects. Knowledge is the main area in the formation of behavior. This study aims to determine the relationship between Knowledge of Hypertension Diet and Diet Compliance in Hypertension Patients at the Wundulako Health Center. This type of research is non-experimental research with a correlation study design (Correlation Study) is a design used in observing the significance of the relationship between 2 variables. This study used a population of 30 people who were treated at the work of the Wundulako Health Center, Kolaka Regency who were identified with a specific purpose or by purposive sampling. The variable of this research is the dependent variable, namely Hypertension Diet Compliance, and the independent variable is the knowledge of hypertension sufferers. The analysis carried out in this study used the Chi-Square statistical test. Chi square test with a confidence level of 95% (α = 0.05) obtained a p value (0.011) <α (0.05) so it can be concluded that there is a relationship between knowledge of hypertension diet and dietary compliance in hypertension sufferers at the Wundulako Health Center.